Phase/frequency deconvolution of seismic signals; International Symposium on Signals, Circuits and Systems (ISSCS 2019) - Kochegurov A. I. Aleksandr Ivanovich; Kochegurova E. A. Elena Alekseevna; Kozlov A. E. Anatoly Evgenjevich; Mongolin A. S. Aleksandr Sergeevich (2019, 2019)
Title screen